Pristine and Hydroxylated Fullerenes Prevent the Aggregation of Human Islet Amyloid Polypeptide and Display Different Inhibitory Mechanisms - Bai, Cuiqin; Lao, Zenghui; Chen, Yujie; Tang, Yiming; Wei, Guanghong (Frontiers in Chemistry, 2020)
Protein aggregation, involving the formation of dimers, oligomers and fibrils, is associated with many human diseases. Type 2 diabetes is one of the common amyloidosis and linked with the aggregation of human islet amyloid polypeptide (hIAPP). A series of nanoparticles are reported to be able to interact with proteins and enhance/inhibit protein aggregation. However, the effects of C60 (a model system of hydrophobic nanoparticle) and C60(OH)8 (a hydroxylated fullerene) on hIAPP aggregation remain elusive. In this study, we investigate the influences of pristine fullerene C60 and hydroxylated C60 on the dimerization of hIAPP using molecular dynamics (MD) simulations. Extensive replica exchange molecular dynamics (REMD) simulations show that isolated hIAPP dimers adopt the amyloid-precursor (β-hairpin) containing β-sheet structure. Both C60 and C60(OH)8 significantly inhibit the β-sheet formation of hIAPP dimer and induce the formation of collapsed disordered coil-rich conformations. Protein−nanoparticle interaction analyses reveal that the inhibition of hIAPP aggregation by C60 is mostly through hydrophobic and aromatic-stacking interactions, while the prevention of hIAPP aggregation by C60(OH)8 is mainly via collective hydrogen bonding and aromatic-stacking interactions. Conventional MD simulations indicate that both C60 and C60(OH)8 weaken the protein−protein interactions and disrupt the β-sheet of hIAPP protofibril. These results provide mechanistic insights into the possible inhibitory mechanism of C60 and C60(OH)8 toward hIAPP aggregation, and provide a valuable reference for the screening of potent amyloid inhibitors.